Model of behavioral attention towards using ICT in universities in Libya - Mohamad, Abdul Ghafarmansor M.M.; Syed Zulkarnain Syed Idrus,; Ibrahim, Amani Ali Elmetwely Ali (Penerbit Universiti Kebangsaan Malaysia, 2018)
Information and communication technology (ICT) is one of the advances utilized as a part of educational tools, and it has been played an effective integration between technology and the lecturer for good quality of teaching and learning. However, a number of researches have been conducted to examine the factors adoption and acceptance of technology, but there is limited on lecturers’ behavioral intention to use ICT in university. Therefore, previous literature has been addressed a series of issues and problem which affect the successful implementation of ICT in the education of Libya such as a lack of policy, poor recourse and lack of skill as well as good infrastructure. The aim of this paper is to examine the factors influencing the lecturers’ intention to use ICT among of the factors suggested by previous literature that may influence lecturers’ intention to use the attitude, behavioral control, Self-Efficacy and ease of use are presented in the following section. Technology acceptance model and theory of planned behavior were adopted to explain the behavioral intention of lecturers to use technology or ICT in universities. The model and theory of Technology acceptance model (TAM) and theory of planned behavior (TPB) were used to explain the behavioral intention of the lecturer to use ICT in Libya universities. The behavioral intention to use technology has an impact on how lectures are delivered to the student, and subsequently expose them to the latest and updated information about education.